Alleviate Effect of Pomegranate Peel Extract in Ameliorating Fluoride-Induced Cytotoxicity, Oxidative Stress in Tetrahymena pyriformis Model - Sabraoui, Talal; Grina, Fatiha; Khider, Taleb; Nasser, Boubker; Eddoha, Rabiaa; Moujahid, Abderahman; Benbachir, Maryem; Essamadi, Abdelkhalid (Biointerface Research in Applied Chemistry, 2022)
Fluoride is a major oligo element found in nature, at excessive amounts can cause enormous harm in mammalian cells. Fruits peel, considered most often as a waste of juice processing, could play an important role in attenuating metal cytotoxicity. The present study evaluated the effect of pomegranate peel (Punica granatum. L) methanolic extract (PPE) on the Fluoride-induced toxicity and redox status in the protozoa Tetrahymena pyriformis. Polyphenols of peel extract were extracted using methanol and characterized by spectrophotometric methods, total phenolic content (TPC), total flavonoids content (TFC), and in vitro, antioxidant properties were assessed using the Folin-Ciocalteu method and DPPH, ABTS, and FRAP. Pomegranate peel is a rich source of phenolic compounds TP (223.21 +/- 15 mg GAE/g dw), TF (52.12 +/- 1.36 mg Qu/g dw) and showed high antioxidant properties DPPH (EC50 0.043 +/- 0.06 mg/ml), ABTS (EC50 0.06 +/- 0.01 mg/ml) and FRAP (1.47 +/- 0.01 mg AA equivalents/g dw). Cells were incubated with fluoride alone and in combination with PPE. NaF (0.8 mM) significantly decreased the cell viability, induced oxidative stress by decreasing antioxidants enzyme activities, and increased intracellular fluoride content. Treatment with NaF in combination with PPE decreases CAT, SOD, and GPx activities and alleviates GSH content. These findings suggest that pomegranate peel biomolecules may have a protective effect against fluoride induced-toxicity.
CRIS-Team WoS Importer:2021-09-03